The human gut microbiome and its metabolic pathway dynamics before and during HIV antiretroviral therapy - Oumar Dolo; Fousseini Coulibaly; Anou M. Somboro; Shan Sun; Modibo Diarra; Aminata Maiga; Soungou Bore; Djeneba B. Fofana; Anne-Genevieve Marcelin; Brehima Diakite; Yaya Kassogue; Jane L. Holl; et al. (Microbiology Spectrum)
ABSTRACT The human gut microbiome consists of highly complex microbial populations that play important roles in disease pathogenesis. Changes in the gut microbiome are associated with HIV infection. However, it is unclear whether gut microbiome dysbiosis is causally linked to disease or whether it simply reflects disease-induced changes in the host immune and metabolic systems. This study aims to describe and compare intestinal microbial compositions and derived metabolic pathways in people living with HIV (PL-HIV) from prior to antiretroviral therapy (ART) to 6 and 12 months after ART initiation, compared to HIV-negative individuals. Whole-genome microbiome sequencing coupled with bioinformatics analysis was used to characterize participants’ intestinal microbial structures and derived metabolic pathways. Pre- and post-ART gut microbiota characterization of PL-HIV revealed substantial dysbiosis compared to HIV-negative people. An enrichment of pro-inflammatory microorganisms was the hallmark of dysbiosis in the PL-HIV pre-ART, with a decline in Proteobacteria at 6 months of ART, continuing until 12 months of ART. Lower proportions of Bacteroidetes were noted pre-ART, but they increased slightly at 6 months of ART before decreasing again at 12 months of ART. Additionally, we reported metabolic changes that are particularly important for health and are associated with dysbiosis both before and post-ART. Alteration of the pyruvate fermentation to the isobutanol metabolic pathway persisted in PL-HIV after 12 months of ART, and this mechanism was correlated with a decrease in Ruminococcus bromii species. ART initiation appears to lead to changes in several crucial metabolic pathways and may not entirely restore the dysbiosis of the gut microbiota caused by HIV.IMPORTANCEResearchers are facing a major challenge in the treatment of HIV infection due to the continuous use of antiretroviral (ARV) molecules. However, regularly monitoring these molecules is necessary because they are not without consequences. They have toxicity and side effects and could also destabilize the intestinal microbiota, which could harm the metabolic pathways essential to good health. This study reveals that ARV treatment only partially restores gut microbiota dysbiosis and alters metabolic pathways due to pathogenic taxa. This provides additional insights into the relationship between antiretroviral therapy and the microbiome, potentially leading to new prevention and treatment strategies such as probiotic/prebiotic or microbiota transplants.